Oncogenic microRNA-155 and its target PU.1: an integrative gene expression study in six of the most prevalent lymphomas - Huskova, Hana; Korecka, Katarina; Karban, Josef; Vargova, Jarmila; Vargova, Karina; Dusilkova, Nina; Trneny, Marek; Stopka, Tomas (International journal of hematology, 2015)
The transcription factor PU.1 and its inhibitory microRNA-155 (miR-155) are important regulators of B-cell differentiation. PU.1 downregulation coupled with oncogenic miR-155 upregulation has been reported in lymphoid malignancies; however, these data have not been studied across different subtypes in relation to clinical outcomes. We studied expression of miR-155 and PU.1 in the six most prevalent human B-cell lymphomas (n = 131) including aggressive (DLBCL, HL, MCL) and indolent (B-CLL/SLL, MZL, FL) types. Levels of miR-155 and PU.1 inversely correlated in DLBCL, B-CLL/SLL, and FL tumor tissues. In HL tissues, an exceptionally high level of miR-155 was found in patients with unfavorable responses to first-line therapy and those who had shorter survival times. PU.1 downregulation was noted in B-CLL/SLL samples positive for the adverse prognostic markers CD38 and ZAP-70. Upregulation of miR-155 and downregulation of PU.1 expression are integral aspects of lymphoma biology that could mark aggressive behavior of some, but not all, lymphoma types.
Keywords: Male; antigeny CD38; lidé středního věku; regulace genové exprese u nádorů; Prevalence; trans-aktivátory; senioři nad 80 let; Aged, 80 and over; nádorové biomarkery; PU.1; Humans; Lymphoma; Middle Aged; Biomarkers, Tumor; senioři; mužské pohlaví; prevalence; Female; Prognosis; ZAP-70 Protein-Tyrosine Kinase; ADP-ribosyl Cyclase 1; MicroRNAs; Aged; microRNA miR-155; ženské pohlaví; lymfom; RNA nádorová; protein-tyrosinkináza ZAP-70; Adult; Trans-Activators; Gene Expression Regulation, Neoplastic; mikro RNA; RNA, Neoplasm; dospělí; lidé; protoonkogenní proteiny; Proto-Oncogene Proteins